N-type Polycrystalline Si Thick Films Deposited on SiNx-coated Metallurgical Grade Si Substrates. Issue 1 (January 2015) - Zhang, Hongliang; Zhu, Liqiang; Guo, Liqiang; Liu, Yanghui; Wan, Qing
Abstract : For photovoltaic applications, low-cost SiN x -coated metallurgical grade silicon (MG-Si) wafers were used as substrates for polycrystalline silicon (poly-Si) thick films deposition at temperatures ranging from 640 to 880 °C by thermal chemical vapor deposition. X-ray diffraction and Raman results indicated that high-quality poly-Si thick films were deposited at 880 °C. To obtain n-type poly-Si, the as-deposited poly-Si films were annealed at 880 °C capped with a phosphosilicate glass. Electrical properties of the n-type poly-Si thick films were investigated by four-probe and Hall measurements. The carrier concentration and electron mobility of the n-type poly-Si film was estimated to be 1.7 × 10 19 cm −3 and 68.1 cm 2 V −1 s −1, respectively. High-quality poly-Si thick films deposited on MG-Si wafers are very promising for photovoltaic applications.